An Experience Of An Adolescent With Non-Suicidal Self-Injury (NSSI) Behaviour: A Narrative Analysis - Nor Dzahirah Binti Adzhari (Universiti Sains Islam Malaysia, 2024)
Matric : 3201257 (FKP)-Restricted until July 2025